The Immediate and Extended Impacts of Poverty Simulations on Multicultural Attitudes and Attitudes Towards Poverty. Issue 3 (16th April 2023) - Merlin-Knoblich, Clare; Summers, LaTonya M.; Abrams, Lyndon
ABSTRACT: Poverty simulations are interactive experiences that simulate the challenges of poverty. We conducted a pre-experimental study to examine the impact of the Community Action Poverty Simulation (CAPS) on participants' attitudes toward poverty and multiculturalism. We surveyed participants' attitudes immediately after the simulation and three months later. Participants ( N = 119) reported statistically significantly improved attitudes toward the stigma and structural perspectives of poverty, as well as multicultural actions before and immediately after the CAPS. Participants (n = 52) also reported significantly improved attitudes toward the stigma of poverty three months after the CAPS compared to before and immediately after.